Evaluative Language in Conclusion Sections of Vietnamese Linguistic Research Articles - Hong, Nguyen Bich (VNU Journal of Foreign Studies; Vol 37 No 3DO - 10.25073/2525-2445/vnufs.4643, 2021)
Evaluative language has recently been of great concern as, according to Hunston, “evaluation is one of the most basic and important functions of language worth studying deeply” (2011, p. 11). However, the term seems to be rather new in Vietnamese linguistic community. In order to shed further light on the use of evaluative language in Vietnamese, this article is to examine how evaluative language is exploited by Vietnamese linguists in the conclusion section of their research articles. This study combines both quantitative and qualitative approaches to analyse the ways explicit evaluative language is used in the corpus of 30 Vietnamese empirical research articles in three reputable journals of linguistics in Vietnam. More specifically, the study investigates various evaluative acts classified in the three systems of the Appraisal Framework (by Martin & White, 2005) including Attitude, Engagement and Graduation. Findings are expected to show outstanding patterns of evaluative language used in this section of linguistic research articles such as the salient occurrence of certain evaluative domains or sub-systems, etc. Results of the study are hoped to be of reference for article writers as well as to enrich literature materials for the fields of evaluative language and academic writing pedagogy in Vietnam.